Children in nature: sensory engagement and the experience of biodiversity - Beery, Thomas; Jørgensen, Kari Anne (Environmental Education Research, 2018)
Given concerns for a severely diminished childhood experience of nature, coupled with alarm for a rapidly diminishing global biodiversity, this article considers the potential for childhood nature experience to be an important part of biodiversity understanding. Findings from two studies are integrated and presented as windows into childhood nature experience to illuminate important aspects of sensory rich learning. In one study from Sweden, semi-structured interviews with adults were conducted and analyzed to explore an understanding of the sensory experience of childhood collecting in nature via participant memories. In the second study, direct observations of children’s play and exploration in an outdoor kindergarten in Norway were conducted and analyzed. Bringing these two studies together for shared analysis is useful for investigating biodiversity experience and understanding. Analysis supports the idea that the experience of biodiversity, actual childhood interaction with variation and diversity with living and nonliving items from nature allows children important learning opportunities, inclusive of biodiversity understanding. The results support practical implications for sensory rich environmental education and underscores the practical importance of childhood access to nature.
Publisher: Routledge _eprint: https://doi.org/10.1080/13504622.2016.1250149
Keywords: Biodiversity understanding; embodied experience; experience of nature; extinction of experience; sensory experience